Staff Rides as Pedagogical Practice. - Lee, So Jin; Szarejko, Andrew A. (PS: Political Science & Politics, 2024)
Political science instructors have started to make use of the "staff ride"—that is, the combined study of a military campaign, structured visits to related sites, and after-action analysis. Our study is the first examination of the potential utility of this pedagogical tool in civilian political science programs. Although the specific knowledge and skills that any given staff ride promotes depend on its content and structure, the potential benefits include four student learning outcomes: (1) staff rides show students how we might draw lessons from the past and apply them to present or future problems; (2) students may derive an enhanced ability to empathize with military and civilian decision makers; (3) staff rides can highlight the normative stakes in politics; and (4) they can foster connections among the participants. This article describes potential benefits of a staff ride, provides detailed instructional models based on the Battle of Gettysburg and the Tet Offensive, and considers ways to replicate these experiences in more accessible formats.